Frontoethmoido-Orbital Mucocele: A Case Report - Sakallıoğlu, Öner; Düzer, Sertaç; Altunsoy, Hasan Baki (Fırat University, 2011)
Mucoceles are the chronic cystic lesions of the paranasal sinuses. They can cause impression to the around tissues despite their benign nature. The patients with frontoethmoid mucocele that extended to the orbit may have complaint with outer pushing of the eye, diplopia and headache in general. For the treatment of mucocele, according to clinical situation of the patient, the external approach or recently advised endoscopic endonasal marsupialisation approach can be performed. We presented a case of frontoethmoido-orbital mucocele that extended to the orbit by destruction of lamina papyracea. No recurrens observed on clinical follow up. The clinical features of the patient and surgical management were discussed with the literature.

Mukoseller, paranazal sinüslerin kronik kistik lezyonlarıdır. İyi huylu olmalarına rağmen kemik erozyonuna yol açarak etraf komşu dokularda basıya yol açabilirler. Orbital bölgeye yayılım yapmış frontoetmoid mukosellerde hastaların başvuru nedenleri sıklıkla gözde dışa itilme, diplopi ve başağrısı olabilmektedir. Mukosel tedavisinde olgunun durumu göz önüne alınarak açık yaklaşımlar veya son zamanlarda önerilen endoskopik endonazal marsupiyalizasyon gibi cerrahi yöntemler uygulanmaktadır. Bu makalede lamina papriseada destrüksiyona yol açarak orbita içine yayılım göstermiş bir frontoetmoido-orbital mukosel olgusu sunuldu. Hastanın klinik takiplerinde nüks izlenmedi. Hastanın kliniği ve uygulanan cerrahi tedavi literatür eşliğinde tartışıldı.
Frontoetmoido-Orbital Mukosel: Olgu Sunumu